Analisis Hubungan Antara Kontrol Diri (Self-Control) dengan Pembentukan Akhlak Mahasiswa Universitas Negeri Medan - Nadhira Eka Putri Prayudi; Nabila Mutiara Syifa; Miranti Agustin; Hapni Laila Siregar (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to analyze the relationship between self-control and the moral development of students at Medan State University. Self-control is an individual's ability to control emotions, impulses, and behavior to align with prevailing moral norms and values ​​in both academic and social settings. This study employed quantitative methods, collecting data through questionnaires distributed to students. The research instrument was used to measure students' levels of self-control and their moral development, as reflected in their attitudes of responsibility, honesty, discipline, and ethical behavior on campus. The data obtained were analyzed to determine the relationship between the two variables. The results showed that students' levels of self-control were considered good and had a positive relationship with moral development. This suggests that students with better self-control tend to display behaviors consistent with prevailing moral values ​​and norms. Therefore, self-control plays a crucial role in the moral development of students, necessitating ongoing efforts by universities to support the development of self-control through character development and academic activities oriented toward moral values.